PENGARUH KEBIJAKAN STRATEGI KOMUNIKASI TERHADAP KINERJA MELALUI KREATIFITAS INDIVIDU KADER POSYANDU - rozita, rozita; Ali Asfar; Jeni Wardi (Journal of Management and Business, 2025)
The aim of this research is to analyze the influence of communication strategies on the performance of posyandu cadres in Tambang District, Kampar Regency, mediated by individual creativity. The population in this study were all posyandu cadres in Tambang District, Kampar Regency with a sample of 80 people. Determining the sample size used the Slovin method and the sampling technique used in this research was non-probability sampling. Data collection techniques using questionnaires and distribution using Google Form. The data analysis technique in this research is Structural Equation Modeling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this research show that communication strategy policies and individual creativity have a positive and significant effect on the performance of posyandu cadres in Tambang District, Kampar Regency. In addition, individual creativity is able to mediate the relationship between communication strategy policies and the performance of posyandu cadres in Tambang District, Kampar Regency.